Environmental education for nurturing nature: Assessment of environmental education in nature protection in Nigeria - Anthony Kola-Olusanya; Peter S. Adewale; Florence Yusuf; Ola T. Odekeye (Social Sciences and Humanities Open, 2025)
Achieving sustainable development in Nigeria is inextricably linked to preserving the country's natural environment, species and biodiversity. However, human activities continue to degrade the natural environment, resulting in the loss of vital resources. Reversing this trend of environmental destruction is imperative. The study investigated the role of environmental education (EE) in promoting nature preservation among Biology teachers in Osun State, Nigeria. A descriptive survey design was employed, and 200 respondents were purposively selected to complete the EE for Nature Protection (EENP) questionnaire. Descriptive statistics and the Mann-Whitney U Test were used to analyse the data. The findings indicated that while the sampled Biology teachers demonstrated a relatively high level of awareness about the importance of EE in nature protection, there is room for improvement. Respondents identified inadequate teaching methods and scarce resources as major factors affecting EE. The result shows that there is no statistically significant difference as indicated by a p-value of 0.11 with a Mann-Whitney U statistic of 4076.00, a Wilcoxon W of 12,332.00 and a Z-score of −1.590. Therefore, efforts to promote EE should be targeted at all teachers. Ministries of Environment and Education should consider providing resources and materials that support EE in schools to engender a culture of sustainability and responsibility among our youth to create a brighter, greener future.